Trade Liberalization and Local Labor Markets in Morocco - Jaime Alfonso Roche Rodriguez; Raymond Robertson; Gladys Lopez-Acevedo; Daniela Ruiz Zárate (Institute of Labor Economics (IZA), 2023)
Morocco's trade liberalization policies have promoted economic progress over the past two decades. However, effects on Morocco's local labor market outcomes vary. By combining three complementary approaches and modeling techniques, this paper estimates: (i) how trade agreements have increased trade flows, (ii) the relationship between trade exposure and mixed local labor market outcomes, and (iii) the relationship between firm employment and exports. Our results show that trade policy has increased trade flows, but this has led to mixed results for workers: increased trade has decreased informality but has failed to improve female labor force participation (FLFP). This appears to be due to a shift from female labor-intensive industries, such as apparel and textile sectors, to capital-intensive sectors that are predominantly male-intensive. Our firm level analysis confirms these results by showing that increase in employment from exports has occurred mainly in male, labor-intensive sectors.
Keywords: F13; F16; O14; O19; 330; trade policy; trade flows; labor market outcomes; firm dynamics